Islamic banks' dilemma between ideals and practice: debt or equity - Sadique, Muhammad Abdurrahman (Universal Publishers, 2010)
Equity financing modes currently adopted by Islamic banks are seen to be based on debt-based formats, originally developed for implementation in in interest-based financing system. With the experience gained over a period, a careful scrutiny of prevalent equity financing techniques could be appropriate in order to assess the level of their success in achieving Islamic economic objectives. With Islamic banking gaining a firm foothold in the banking and commercial sectors, a more dynamic approach to promulgating the ideals of equity participation appears timely.